Profile of the Use of Oral Antidiabetic Drugs in Outpatinets at the Lonrong Health Center, Ponre District, Bone Regency in 2023 - Sukmawati Sukmawati; Maulya Faradina; Ira Asmaliani (Journal of Pharmaceuticals and Natural Sciences, 2026)
Diabetes mellitus is a degenerative chronic disease characterized by impaired insulin secretion, impaired insulin production and impaired insulin sensitivity. The use of diabetes mellitus drugs can cause problems if the therapeutic goals are not appropriate, one of which is due to the improper selection of drugs so that the therapeutic goals are not effective. This study aims to analyze the profile of the use of antidiabetic drugs in outpatients at Lonrong Health Center in 2023 based on the parameters of the right drug, the right dose, the right indication, and the right time of administration. This study is non-experimental research with a retrospective descriptive design. The sampling technique used is purposive sampling. The sample in this study is medical record data of diabetic mellitus patients in 2023 who meet the inclusion and exclusion criteria. The results showed that of the 50 samples consisting of 41 women (82%) and 9 men (18%), the prevalence of age was dominated around > 60 years (38%). In the rational analysis of drug use, it was found that the indication accuracy was 100%, drug accuracy was 82%, correct dosage was 100% and punctuality of administration was 100%.